Predicting longevity from the line of life: is it accurate? - Lucas, Teghan; Dhugga, Amrita; Henneberg, Maciej (Anthropological Review, 2019)
Palmistry or Chiromancy is the art of reading lines on the palm of the hands. Today, many researchers believe that the lines on the palms of the hands can predict the individual’s future. Computer programs are being designed which can automatically read the lines on the palm of the hand. One popular theory is that the length of the line of life will indicate lifespan. This theory was investigated in 1974 by Wilson and Mather who found no significant correlation between life expectancy and the length of the line of life. In 1990 Newrick and colleagues found a significant correlation as measured on 100 cadavers. These conflicting investigations are the only existing studies which have explored the relationship between palmistry and longevity. Since then no other study has validated nor disproven these claims. A total of 60 cadavers donated to The University of Adelaide were used in this study. Total hand length and the line of life length were measured on all cadavers. The age at and cause of death were also recorded. Linear regressions were used to establish any correlations between longevity and the length of the line of life. No significant correlations were found. There was also no significant difference between males and females or the right or left hands. As no significant correlations were found between longevity and the line of life all efforts at producing more reliable and automatic ways to read the lines are futile. This study puts to rest any debate surrounding the use of the line of life in palmistry as introduced by Newrick and colleagues.